The casebook and socratic methods in the United States legal education - Truong, Hai Ha (2020)
The casebook method is the usage of casebooks containing court decisions of actual cases as teaching materials; and the Socratic method is the in-class dialogue or questioning employed by the teacher. They were first introduced in American legal education by Former Harvard Law professor Christopher Columbus Langdell in the 1870s. Although the heated debate as to the effectiveness of the methods have never ceased since then, the casebook and Socratic methods remain the predominant teaching methods in American till the current day. This thesis paper presents a brief history of how the two methods came into existence in the American legal education, analyzes the two methods in practice along with their supporting and opposing critiques, and offers some implications for Vietnamese higher education. From the information collected and processed by means of document comparative analysis methodology, it was found that despite all the critiques, the casebook and the Socratic methods have proved to be especially effective in preparing students for their future careers. Based on such analysis, some implications for Vietnamese higher education can be realized. First, it is necessary for Vietnamese higher education to prepare students with practical skills to meet the demands of the labor market. Secondly, teachers and learners’ interaction in Vietnamese higher education should be increased. Last but not least, Vietnamese learners’ self-study ability needs to be developed. These can be done by learning the appropriate teaching methods from more advanced countries. However, Vietnamese social, economic and other related features need to be taken into consideration before any adoption and/or adaption is made